2014
DOI: 10.1038/ncomms4429
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous precessional motion of multiple domain walls in a ferromagnetic nanowire by perpendicular field pulses

Abstract: Magnetic storage and logic devices based on magnetic domain wall motion rely on the precise and synchronous displacement of multiple domain walls. The conventional approach using magnetic fields does not allow for the synchronous motion of multiple domains. As an alternative method, synchronous current-induced domain wall motion was studied, but the required high-current densities prevent widespread use in devices. Here we demonstrate a radically different approach: we use out-of-plane magnetic field pulses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…In particular, the promising concept of "race-track memory" [1,3] demands a well controlled motion of the DW along a nanowire. In this context, several works have studied the controlled displacement of DWs in stripes [4][5][6][7][8][9] and cylindrical wires [10][11][12]. Such studies have revealed that geometry plays a fundamental role in the DW dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the promising concept of "race-track memory" [1,3] demands a well controlled motion of the DW along a nanowire. In this context, several works have studied the controlled displacement of DWs in stripes [4][5][6][7][8][9] and cylindrical wires [10][11][12]. Such studies have revealed that geometry plays a fundamental role in the DW dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, using a TMF is the easiest way. Thus it is of great value to systematically investigate the TDW dynamics under TMFs, which is also an issue of interest in the academic community in recent years [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Most existing works are numerical [43][44][45][46][47] or experimental [48][49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Although DWs in soft-ferromagnetic nanowires can be propagated at modest applied fields $10 Oe, 3 neighbouring DWs travel in opposite directions, making synchronous data transport impossible unless complex "ratcheted" nanowires 4,5 or field pulses with intricate spatial 6 or temporal profiles 7 are employed. Moving DWs via spin-torque effects is a more attractive approach, since neighbouring DWs travel uni-directionally.…”
mentioning
confidence: 99%